THE USE OF POSITIVE BILEVEL PRESSURE IN PATIENTS IN THE POSTOPERATIVE GASTROPLASTY (CIPEEX, 2024)
GASTROPLASTY IS A FORM OF TREATMENT FOR OBESE PEOPLE. FOR ITS REALIZATION, A RIGOROUS ANALYSIS OF THE PATIENT BY THE MULTIDISCIPLINARY TEAM IS NECESSARY, EVALUATING THE PHYSIOLOGICAL, NUTRITIONAL AND PSYCHOLOGICAL CONDITIONS OF THE PATIENT. NON-INVASIVE VENTILATION IN BILEVEL POSITIVE PRESSURE MODE (BIPAP) HAS BEEN USED IN THE PREVENTION AND TREATMENT OF RESPIRATORY COMPLICATIONS, IN ORDER TO RECOVER AND REHABILITATE THE PATIENT EARLY IN THE POSTOPERATIVE PERIOD OF BARIATRIC SURGERY. THE OBJECTIVE TO SURVEY THE SCIENTIFIC LITERATURE ON THE USE OF BILEVEL POSITIVE PRESSURE IN THE POSTOPERATIVE PERIOD OF GASTROPLASTY, ANALYZING THE PHYSIOLOGICAL EFFECTS AND THE FREQUENCY OF USE OF BIPAP. METHODOLOGY IS INTEGRATIVE REVIEW, WITH BIBLIOGRAPHIC SURVEY IN THE VIRTUAL HEALTH LIBRARY, CAPES (COORDINATION FOR THE IMPROVEMENT OF HIGHER EDUCATION PERSONNEL) AND U.S. NATIONAL LIBRARY OF MEDICINE THESAURUS PUBMED JOURNALS. STUDIES WERE INCLUDED THAT ADDRESS THE PROPOSED THEME AND PUBLISHED IN THE LAST 6 YEARS (2016-2022), IN PORTUGUESE, ENGLISH AND SPANISH, AVAILABLE IN FULL, FROM THE INTEGRATION OF THE CATEGORIES OF DESCRIPTORS €ŒGASTROPLASTY€, €ŒBARIATRIC SURGERY€, €ŒBARIATRIC", "INTERMITTENT POSITIVE PRESSURE VENTILATION", "TWO LEVELS OF POSITIVE PRESSURE", "MECHANICAL VENTILATION", "NON-INVASIVE VENTILATION", "COMPLICATIONS", "PULMONARY ATELECTASIS". AMONG THE FIVE PAPERS FOUND, WITH A TOTAL OF 5,461 PARTICIPANTS STUDIED, ALL UNDERWENT GASTROPLASTY. PATIENTS WHO USED BIPAP SHOWED A SIGNIFICANT IMPROVEMENT IN THE IMMEDIATE POSTOPERATIVE PERIOD, WITH CONTROL OF OXYGENATION AND PULMONARY FUNCTIONALITY. PATIENTS WHO DID NOT USE OR WERE MANIPULATED LATE, HAD RESPIRATORY COMPLICATIONS SUCH AS ATELECTASIS AND PNEUMONIA, OR NEEDED TO BE INTUBATED. IT IS EVIDENT THAT THE USE OF POSITIVE BILEVEL PRESSURE IN THE POSTOPERATIVE PERIOD OF GASTROPLASTY CAN REDUCE THE RISK OF RESPIRATORY COMPLICATIONS.
Keywords: Academic management; Reservations; Resources; Efficiency